Gender Dimensions of Education Access and Achievement in Sri Lanka - Aturupane, Harsha (World Bank, Washington, DC, 2018)
Sri Lanka is a lower-middle income country with an impressive record of achievementsin economic and human development. Despite 26 years of conflict, Sri Lanka, an island countrywith a population of 20.6 million has stood out from its regional counterparts with high levels ofhuman development. Sri Lanka’s score in the Human Development Index (HDI) is 0.766—whichput the country in the high human development category (UNDP 2016). The country has also hasalso witnessed significant economic growth in recent years: in 2017, its per capita income was3,842 (UDS), more than four times that of its GPD in 2002. With these achievements, it has nowadvanced the economic ladder, from a low to a middle-income country.2. Policy makers are keen to build on the country’s successes and to ensure that the benefitseconomic growth are distributed equitably in the population. Sri Lanka is poised to grow, witha development strategy expressly aimed at fostering strong and equitable growth for its entirepopulation (Bhatta, Ebenezer and Nyugen 2014). Despite its achievements in human development,the country has had persistent pockets of inequity, by region, as well as population sub-group- andsocial inequity, whether caused by gender, economic disadvantage, or any other factor, over a longperiod of time, that has limited the potential benefits of growth (Aturupane 1999a; Dundar, Millot,Riboud, Shojo, Aturupane, Goyal, and Raju 2017). Sri Lanka’s policy makers recognize this andunderstand the importance of ensuring equitable growth.